2019
DOI: 10.1039/c9cc04610k
|View full text |Cite
|
Sign up to set email alerts
|

A room temperature multivalent rechargeable iron ion battery with an ether based electrolyte: a new type of post-lithium ion battery

Abstract: The feasibility of developing a rechargeable iron ion battery is demonstrated for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…Recent research has also looked into inexpensive cations suchas sodium (Na), and for multivalent cations that could lead to higher energy through increasing the number of electrons, e.g. magnesium (Mg) and even having multiple possible oxidation states as iron (Fe)[221,222]. Also, of recent interest is the Zinc-Air battery, where…”
mentioning
confidence: 99%
“…Recent research has also looked into inexpensive cations suchas sodium (Na), and for multivalent cations that could lead to higher energy through increasing the number of electrons, e.g. magnesium (Mg) and even having multiple possible oxidation states as iron (Fe)[221,222]. Also, of recent interest is the Zinc-Air battery, where…”
mentioning
confidence: 99%
“…Among vanadium oxides, vanadium pentoxide V 2 O 5 , which has the highest oxygen content 1 , is of paramount importance since its properties are highly sensitive to external factors, so it is used in photocatalysts 2 , chemical actuators 3 , optical fibers 4 , gas sensors 5 7 , and electrochromic devices 8 . The structure of V 2 O 5 is best described as an arrangement of square pyramid VO 5 units forming layers, which enables high ion storage capacity for batteries 9 12 . Recently, it has been found that reversible changes in V 2 O 5 resistivity could be triggered by voltage 13 or temperature 14 , which could be helpful for neuromorphic computing applications 15 and photonic device architectures 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Though lithium-ion batteries continue to dominate worldwide as energy storage devices, sodium-ion batteries (SIBs) have been gaining attention due to their extensive research. [1][2][3] According to research and development, sodium-ion batteries [4][5][6] are the next generation batteries for energy storage applications, among all other types of batteries, including magnesium-ion, 7,8 aluminumion, 9 potassium-ion, 10 calcium-ion, 11 iron-ion, 12 zinc-ion batteries. 13 The sodium has a low redox potential (−2.71 V vs. standard hydrogen electrode [SHE]) comparable to lithium metal (−3.04 V vs. SHE).…”
Section: Introductionmentioning
confidence: 99%